(untitled) (Research, Society and Development, 2020)
This research aimed to verify the dietary profile of Crossfit practitioners and their repercussions, already published and published in the literature. Study of integrative literature review, of qualitative and exploratory nature, with theoretical approach. The research results in information regarding the dietary profile of Crossfit practitioners. The search for the articles was carried out in online databases: Medline (Medical Literature Analysis and Retrieval System Online), PubMed (National Library of Medicine) and Google Scholar, published from 2016 to 2020. To search for bibliographic material, the following keywords were used: “Crossfit”, “food profile”, “physical activity” and sports nutrition. In the studies examined, it can be seen that adequate nutritional strategy, both quantitatively and qualitatively, according to the type of exercise practiced influences the results of crossfit practitioners. In one article, several inadequacies were found in relation to the recommendations, such as reduced caloric intake and low consumption of carbohydrates. In addition, there was an insufficient intake of some micronutrients, only in the group of women, of the minerals iron and calcium, and as vitamins E and folate. Thus, through specialized studies, it is concluded that inappropriate eating habits directly reflect on the performance of Crossfit practitioners. Therefore, adhering to an adequate nutritional strategy, both quantitatively and qualitatively, is a promising method, since it benefits health, well-being and optimizes the performance of practitioners.